The effect of angular mismatch between vertebral endplate and vertebral body replacement endplate on implant subsidence. - Mohammad-Shahi, Mohammad H; Nikolaou, Vassilios S; Giannitsios, Demetrios; Ouellet, Jean; Jarzem, Peter F (J Spinal Disord Tech, 2013)
STUDY DESIGN: Comparative biomechanical study. OBJECTIVE: To determine whether an angular mismatch between the vertebral body replacement (VBR) endplate and the simulated foam vertebral endplate leads to accelerated subsidence in a cyclic compression model of the VBR-vertebra interface. SUMMARY OF BACKGROUND DATA: One of the main complications of the VBR surgery is postoperative subsidence and collapse of the VBR implant into the adjacent vertebral bodies. Although numerous factors affecting intervertebral cage subsidence have been cited, few studies have proposed factors responsible for VBR cage subsidence. METHODS: Hardwood blocks at 0-30-degree angles and polyurethane foam blocs have been used as base for this experimental setting. One end of the Synex (Synthes) expandable cage was attached to a material testing machine. The endplate of the implant was placed at a similar spot on the block in such a manner that there was an exact match between the Synex endplate and the foam block at 0 degrees, subsequent angled blocks would tilt the foam endplates by the 10-, 20-, and 30-degree increments as needed. Cyclic axial loads were applied in 9 load-unload cycles. RESULTS: Five samples were tested at each mismatch angle (0, 10, 20, and 30 degrees), for a total of 20 trials. Implant subsidence significantly increased for each 10-degree increase in mismatch angle. This effect, however, did not follow a uniform trend at all angles. The curve appeared exponential at 0 degree of angular mismatch, became linear at 10-20 degrees of mismatch, and then demonstrated some ability to resist load at 30 degrees, leading to a plateau at the higher loads. CONCLUSIONS: Increasing mismatch angles are an important factor in leading to increased cage subsidence into polyurethane blocks. Consequently, the incidence of subsidence in the clinical setting could be reduced by paying careful attention to ensuring that both the prosthetic and bony endplates are well apposed at the end of surgery.
Keywords: Biomechanical Phenomena; Female; Humans; Intervertebral Disc; Middle Aged; Polyurethanes; Prostheses and Implants; Weight-Bearing